Comparative Analysis of Startup Valuation Using the Dave Berkus Method and Scorecard Method in a Case Study of Pesona Plastic: in a Case Study of Pesona Plastic - Gede Siantie; I Gede Juliana Eka Putra; I Gusti Agung Prabandari Tri Putri (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to compare startup valuation results using The Dave Berkus Method and the Scorecard Method on Pesona Plastic, an early-stage social and environmental startup engaged in plastic waste recycling into furniture products in Bali. The research applies a qualitative descriptive approach with data collection through observation, semi-structured interviews, and documentation. The valuation results show that The Dave Berkus Method produces a higher valuation of IDR 3,900,000,000 compared to the Scorecard Method, which yields IDR 3,170,700,000. The difference is mainly caused by variations in assessment focus, where The Dave Berkus Method emphasizes non-financial and internal potential factors such as business ideas, prototypes, team quality, strategic relationships, and early market acceptance. In contrast, the Scorecard Method relies more on market comparisons and industry benchmarks, which are limited for early-stage startups. Considering the development stage and characteristics of Pesona Plastic, The Dave Berkus Method is considered more relevant and representative for valuing the startup. This study contributes to startup valuation literature by providing empirical evidence on the suitability of valuation methods for early-stage social and environmental startups..